A Sexism Analysis in English Textbook Used in Indonesian Schools' 7th Grade Entitled: “When English Rings a Bell” Published By the Ministry of Education and Culture - Suryawati, Sri Suci; Kholid, M Ridho; Tipani, Ayu (English Education: Jurnal Tadris Bahasa Inggris, 2023)
Sexism is a foundation where there is unequal treatment between men and women in society. This unequal treatment emphasizes the dominance of men over women. This research analyzed sexism in English textbook 7th grade entitled “When English Rings a Bell” Published by the Ministry of Education and Culture at  Indonesia.  This research  used  descriptive qualitative method  and  used  six criteria of sexism based on NCTE guidelines for gender-fair use of language and also Porreca’s study to analyze the data, that are includes: generic he, generic man,  titles,  labels  and  names,  occupational  roles,  omission,  firstness.  The technique of data analysis of this research adopted from Miles and Huberman theory. The aims of this research is to know the dominant criteria of sexism found in English textbook 7th grade entitled “When English Rings a Bell” Published by Ministry of  Education and  Culture  at Indonesia.  The results of  this research shows that there are 5 criteria of sexism found in the English textbook 7th grade entitled “When English Rings a Bell” Published by Ministry of Education and Culture at Indonesia, that are includes: generic man, titles, labels and names, the occupational, omission, firstness. The dominant criteria’s of sexism found is omission criteria. Key words:     EFL textbook, sexism, society